2016
DOI: 10.1038/srep37842
|View full text |Cite
|
Sign up to set email alerts
|

Cellular reactions to long-term volatile organic compound (VOC) exposures

Abstract: Investigations of cellular processes initiated by volatile organic compounds (VOCs) are limited when modelling realistic long-term exposure scenarios at low concentrations. Exposure to indoor VOCs is associated with a range of adverse effects, but data on molecular changes at regulatory threshold limits are lacking. Activity analysis of VOC in vitro can be a valuable complement to inhalation toxicological evaluations. We developed an exposure platform that generates a stable VOC atmosphere and allows the expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Likewise, human tracheal fibroblast Hs 680.Tr cells treated with media containing 100 µM (3 ppm) formaldehyde for 4 h caused ~ 50% reduced viability (determined by MTT colorimetric assay) 88 . Conversely, studies in A549 cells detect a negligible reduction in viability after 0.5 ppm formaldehyde exposure for 72 h using the ALI, and in BEAS-2B cells show over 90% viability over a period of 6 h with exposure concentrations up to 15 ppm 42,89 . The latter observation, also based on BEAS-2B cells, is most consistent with our results, albeit using much higher levels of formaldehyde exposures.…”
Section: Discussionmentioning
confidence: 91%
“…Likewise, human tracheal fibroblast Hs 680.Tr cells treated with media containing 100 µM (3 ppm) formaldehyde for 4 h caused ~ 50% reduced viability (determined by MTT colorimetric assay) 88 . Conversely, studies in A549 cells detect a negligible reduction in viability after 0.5 ppm formaldehyde exposure for 72 h using the ALI, and in BEAS-2B cells show over 90% viability over a period of 6 h with exposure concentrations up to 15 ppm 42,89 . The latter observation, also based on BEAS-2B cells, is most consistent with our results, albeit using much higher levels of formaldehyde exposures.…”
Section: Discussionmentioning
confidence: 91%
“…To the best of our knowledge, fewer than 20 peer-reviewed articles have been published on studies involving the MucilAir model, and less than half of these address the effects of air pollutants. [22][23][24][25] Furthermore, none of these studies (including those based on other ALI cell models [26][27][28] ) have focused on the effects of long-term exposure (i.e. lasting several weeks).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that most of the samples collected during pesticide application had detectable VOCs and SVOC compounds, in part because the farmers hung the mechanical sprayer on their shoulders, very close to their breathing zone. Since farmers may have been exposed to chemicals including VOCs, SVOCs, and pesticides, long-term exposure and the possible resultant health effects have been suggested for further study [54][55][56][57][58]. Eleven VOCs compounds were found in these air samples including Methlylene Chloride; Ethylbenzene; o-Xylene; m-Xylene; p-Xylene; Styrene; 1-Methyl Ethylbenzene; Tert-Butyl Benzene; 1, 3, 5-Trimethyl Benzene; 1-Methyl Propyle Benzene; and 1, 4-Dichloro Benzene.…”
Section: Discussionmentioning
confidence: 99%